2021
DOI: 10.3390/ani11051382
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge on Functionality and Potential Therapeutic Uses of Donkey Milk

Abstract: The increase of knowledge on the composition of donkey milk has revealed marked similarities to human milk, which led to a growing number of investigations focused on testing the potential effects of donkey milk in vitro and in vivo. This paper examines the scientific evidence regarding the beneficial effects of donkey milk on human health. Most clinical studies report a tolerability of donkey milk in 82.6–98.5% of infants with cow milk protein allergies. The average protein content of donkey milk is about 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 89 publications
(187 reference statements)
0
24
0
2
Order By: Relevance
“…Furthermore, other studies have shown that e LF as a minor component in DM can be easily digested by gastric and duodenal juice. Thus, it has been suggested that LF can play its biological role in vivo mainly through its bioactive peptides derived from digestion (Martini et al, 2021). Recent studies also showed that antimicrobial activity of LF was further increased after in vitro simulated gastrointestinal digestion (Martini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, other studies have shown that e LF as a minor component in DM can be easily digested by gastric and duodenal juice. Thus, it has been suggested that LF can play its biological role in vivo mainly through its bioactive peptides derived from digestion (Martini et al, 2021). Recent studies also showed that antimicrobial activity of LF was further increased after in vitro simulated gastrointestinal digestion (Martini et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it has been suggested that LF can play its biological role in vivo mainly through its bioactive peptides derived from digestion (Martini et al, 2021). Recent studies also showed that antimicrobial activity of LF was further increased after in vitro simulated gastrointestinal digestion (Martini et al, 2021). Similarly, it was suggested that α-lactalbumin possesses bactericidal activity only after its partial digestion by endopeptidases (Vincenzetti et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Donkey milk has potential antibacterial and immunoprotective effects that could prove useful for protecting vulnerable newborns or promoting adaptive immunity in infants [ 27 , 28 ]. In this study, we identified several immunoprotection-related genes that were upregulated in the lactating jenny mammary gland but not during the nonlactating period.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the low protein and casein contents of equid milk make these milks suitable for children with cow milk protein allergy (Vincenzetti et al, 2017). Equid milk has nutritional similarities to human milk in terms of protein content and caseins, the most allergenic cow milk components (Martini et al, 2021). Their primary structure is very similar to those of human milk (Cunsolo et al, 2017).…”
Section: Mammary Gland Physiology and Farm Management Of Dairy Mares And Jenniesmentioning
confidence: 99%